A Systematic Review Comparing Conservative and Surgical Approaches in the Management of Patellofemoral Instability - Vito Pavone; Emanuele Perricone; Giorgio Santi Pirrone; Alessia Caldaci; Michele Iacona; Marco Sapienza; Gianluca Testa (Applied Sciences)
Background: Patellofemoral instability is a pathological condition that is characterized by altered joint congruence, which manifests as episodes of subluxation or dislocation of the patella. The aim of this study was to systematically review the literature on this condition by comparing the results of various studies evaluating the effectiveness of surgical versus conservative treatment approaches for patellar instability, particularly in patients experiencing a first episode of patellar dislocation. Methods: The research was conducted using three different databases: PubMed, Cochrane Library, and PEDro. Both randomized controlled trials (RCTs) and non-randomized studies of interventions (NRSIs) with full text availability were included. All articles were in English, and no temporal limits were imposed during the search. Results: In total, 10 articles met the inclusion criteria and were included in the systematic review. The standard for statistical significance was p < 0.05. The statistical analysis of re-dislocation rates indicated a statistically significant difference between the conservative and surgical groups (p = 0.023). The statistical analysis also showed that the mean Kujala score was significantly lower in the non-operative group (80.94) than the surgical group (89.83) (p = 0.017). These results indicate that surgical treatment is significantly more effective in reducing re-dislocation rates than conservative treatment and has better Kujala scores than conservative treatment. Conclusions: A reduction in the re-dislocation rate and improved scores on subjective tests related to pain and quality of life were observed with surgical treatment. Nevertheless, a higher level of evidence is needed to more clearly and accurately determine the most effective treatment approach.